The Motion Detection on Video Surveillance by Using Background Subtraction - et. al, Ahmad Fauzi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Video surveillance has been widely used for monitoring incidents at facilities and public places. Surveillance systems that are used in general are still using people as video surveillance. The surveillance system has been developed with a semi-automatic and automatic system. Video surveillance in this study aims to detect motion in the room by estimating static cameras and static backgrounds. Object detection starts by reading the video file and the number of video frames. The background subtraction method is used to find differences between frames by reducing the current frame to the background frame. The difference in pixels that appear in the current frame shows the pixel location of a motion. Through threshold operations in the range 0.2 to 0.3, binary images of motion can be produced better. Noise problems that arise are resolved using morphological operations in the form of holes or points. The results of research on videos with a size of 1,280 x 720 pixels and FPS 25 can detect motions marked with bounding boxes.